Ubezpieczenia od niedołęstwa (typu Long-Term Care) - produkty i modele aktuarialne - Jackowska, Beata (Long-Term Care Insurance -Products and Actuarial Models, 2008)
In the developed countries by reason of demographic aging of populations importance of long term care (LTC) increases. LTC insurance provides income support for the elderly person who needs nursing or medical care. This paper presents time-continuous, multistate approach to the actuarial structure of some LTC insurance products. This work is structured as follows: 1. The increase in frailty risk in the developed countries. 2. The description of basic LTC insurance products. 3. Multistate models for some LTC insurances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 88-96